Machine learning-based approach on predicting online shopping addiction using EEG signals - Nawer, Nafisa; Jahan, Nazia; Fuwad, Md. Mubtasim; Bhuiyan, Mehedi Hasan; Kabir, Imtiaz (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.